The effect of brood and queen pheromones, as well as the colony environment, in the success of Apis mellifera capensis social parasites - Hanekom, Marc C. (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MSc (Botany and Zoology))--University of Stellenbosch, 2007.